2018
DOI: 10.3390/molecules23051100
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenases: From Improved Performance to Potential Microbial Dehalogenation Applications

Abstract: The variety of halogenated substances and their derivatives widely used as pesticides, herbicides and other industrial products is of great concern due to the hazardous nature of these compounds owing to their toxicity, and persistent environmental pollution. Therefore, from the viewpoint of environmental technology, the need for environmentally relevant enzymes involved in biodegradation of these pollutants has received a great boost. One result of this great deal of attention has been the identification of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 284 publications
(408 reference statements)
0
50
0
Order By: Relevance
“…Other non-respiratory bacterial dechlorination processes also exist and use a variety of different hydrolytic or oxidative dehalogenase enzymes (reviewed in Fetzner, 1998; Ang et al, 2018). These processes result in the removal of chlorine atoms from an organic backbone with no energetic benefit to the organism, other than the liberation of organic carbon that can be used catabolically (Fetzner, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other non-respiratory bacterial dechlorination processes also exist and use a variety of different hydrolytic or oxidative dehalogenase enzymes (reviewed in Fetzner, 1998; Ang et al, 2018). These processes result in the removal of chlorine atoms from an organic backbone with no energetic benefit to the organism, other than the liberation of organic carbon that can be used catabolically (Fetzner, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These processes result in the removal of chlorine atoms from an organic backbone with no energetic benefit to the organism, other than the liberation of organic carbon that can be used catabolically (Fetzner, 1998). The most common of these so-called non-reductive dehalogenase enzymes include haloalkane dehalogenases, 2-haloacid dehalogenases, 4-chlorobenzoyl-CoA dehalogenase, and fluoracetate dehalogenase, all of which function via hydrolytic dehalogenation (Ang et al, 2018), and a variety of mono- and dioxygenase enzymes that are specific to dechlorination, such as 2-halobenzoate 1,2-dioxygenase and chlorobenzoate dioxygenase (Fetzner, 1998). Haloalkane dehalogenases have been shown to be capable of dechlorinating contaminants, including hexachlorocyclohexane and dichloroethane (Sharma et al, 2006; Munro et al, 2017), and may also be capable of dechlorinating Cl-NOM, as suggested by Weigold et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…This group of enzymes catalyses the cleavage of the carbon-halogen bond of organohalogen compounds and has potential applications in the chemical industry and bioremediation. Hydrolytic dehalogenation is commonly performed by haloalkane dehalogenase, 2-haloacid dehalogenase and 4-chlorobenzoyl-CoA dehalogenase, while reductive respiratory dehalogenation is carried out by organisms which derive energy from the dehalogenation process [85,86]. Haloalkane dehalogenases convert haloalkanes to their corresponding alkanes, halides and protons [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…This group of enzymes catalyzes the cleavage of the carbon-halogen bond of organohalogen compounds and has potential applications in the chemical industry and bioremediation. Hydrolytic dehalogenation is commonly performed by haloalkane dehalogenase, 2-haloacid dehalogenase, 4-chlorobenzoyl-CoA dehalogenase, while reductive respiratory dehalogenation is carried out by organisms which derive energy from the dehalogenation process (Ang et al 2018;Temme et al 2019) and the literature is replete with reports of organisms spanning several genera, including Rhizobium and Bradyrhizobium, which express varieties of these proteins (van der Ploeg et al 1991, Holloway et al 1998, Stringfellow et al 1997).…”
Section: Discussionmentioning
confidence: 99%